Implementation determinants of safer smoking supplies in U.S. syringe services programs - William H. Eger; Angel K. Gomez; Kirstin Kielhold; Tyler S. Bartholomew; Angela R. Bazzi (Implementation Science Communications)
Abstract Background The prevalence of smoking opioids and other unregulated drugs has increased across the United States (U.S.) since 2000. Improved access to safer smoking supplies may reduce the health consequences of inhalation while helping to engage more people who use drugs in syringe services programs (SSPs); however, the landscape of safer smoking supply implementation is understudied. Methods From November 2023–January 2024, we surveyed representatives of U.S. SSPs to assess safer smoking supply implementation across contextual domains of the Exploration, Preparation, Implementation, and Sustainment (EPIS) framework. Descriptive statistics were used to describe determinants across the phases of safer smoking supply implementation. Poisson regression identified factors associated with implementation. Results Among 118 organizations responding to the survey, most received state funding (83%), were community-based organizations (CBOs; 74%), and served urban jurisdictions (62%). The majority (67%) were already providing safer smoking supplies; 16% were exploring implementation and 11% were not. On average, safer smoking supply implementation occurred more recently than the provision of syringes (1–2 years ago vs. > 5 years ago), with participant request being the most common motivation for implementation (84%). Additional facilitators of safer smoking supply implementation were organizational prioritization (65%) and internal leadership support (57%). Factors significantly associated with safer smoking supply implementation included being from the Northeastern or Western regions (vs. the U.S. South), serving exurban communities, being a CBO, receiving foundation funding, receiving private donations from fundraising, and offering syringes and other injection alternatives (e.g., safer snorting supplies). Receiving federal funding, fear of external community opposition, internal leadership opposition, and respondent uncertainty about changing demand for safer smoking supplies (vs. perceiving that demand has not changed) were negatively associated with implementation. Conclusions Determinants in the inner context, like organizational prioritization of safer smoking supplies and internal leadership support, may facilitate safer smoking supply implementation, while specific outer context factors (e.g., funding, regional policies) may inhibit implementation. Flexible policies and funding structures and further research to build and disseminate evidence on the benefits of safer smoking supplies are needed to expand the implementation and scale-up of this prevention service within U.S. SSPs.